Features of creating pedagogical conditions for forming social competence in the conditions of professional music education - Luhova, Viktoriia; Levandovskyi, Mykhailo (Professional Art Education, 2025)
The article aims to reveal the essence of pedagogical conditions as a system of specially organized components within the educational process that influence the formation of social competence among students of a specialized music college. The study focuses on identifying the characteristics of the musical educational environment and its role in socialization and personality development. Methods and methodology. The research employs theoretical analysis and synthesis of pedagogical literature, as well as an interpretative approach to understanding the specifics of musical education as a socio-cultural phenomenon. Empirical observations of educational interactions and collective creative activities in music learning contexts are also considered. Scientic novelty. This study provides a comprehensive conceptualization of pedagogical conditions that support social competence development in music students by emphasizing the unique features of the musical educational environment – such as intensive interpersonal interaction, collective creativity, and emotional expressiveness. Results. It is established that the musical arts function as an effective medium of socialization by facilitating the comprehension of social phenomena, moral norms, and value orientations. The research highlights the integration of individual lessons, group performances, stage activity, and socio-cultural initiatives as critical factors for fostering empathy, communication skills, responsibility, cooperation, and self-expression. Key pedagogical conditions are identified, including subject-subject interaction, collective activities, nurturing educational environments, student involvement in social initiatives, use of interactive teaching methods, and the cultivation of reflective practice. The systemic implementation of these conditions significantly contributes to the development of socially mature personalities among music students. Conclusions. The study concludes that harmonizing professional training with social development within an arts educational institution creates favorable conditions for students’ holistic growth. This integrated approach enhances not only professional competencies but also essential social qualities necessary for successful interaction in professional and social spheres.